The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.22616/erdev2017.16.n113
|View full text |Cite
|
Sign up to set email alerts
|

The physical mechanical properties evaluation of experimental granulated organic compost fertilizer

Abstract: Abstract. Currently, there are searches for new and more rational ways to use biological waste for new forms of energy, creating fertilizers, building materials and other products. One kind of this biodegradable waste management is pelleting as the processing of recyclable materials into organic products. In the EU today only 5 % of bio-waste is recycled. According to estimates, if more bio-waste was recycled, it could replace up to 30 % of non-organic fertilizers. Currently, the EU imports around 6 million to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Bulk density of poultry manure with litter raw material was 647.1 ± 4.05 kg•m -3 . This is a higher rate compared to cattle manure compost raw material bulk density (556.4 ± 5.81 kg•m -3 ) [13], or composted pig manure raw material (525.8 ± 56.06 kg•m -3 ) [14]. Average moisture content of the prepared mill after artificially drying in the ventilation canal was 11.2 ± 1.4% (Table 2).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Bulk density of poultry manure with litter raw material was 647.1 ± 4.05 kg•m -3 . This is a higher rate compared to cattle manure compost raw material bulk density (556.4 ± 5.81 kg•m -3 ) [13], or composted pig manure raw material (525.8 ± 56.06 kg•m -3 ) [14]. Average moisture content of the prepared mill after artificially drying in the ventilation canal was 11.2 ± 1.4% (Table 2).…”
Section: Resultsmentioning
confidence: 95%
“…Compared to previous studies of cattle manure compost granules, it may be seen that granules under the force of 425 N in horizontal compression disintegrated totally. Granules with molasses addition reached 491 N in horizontal direction [13], average pig manure compost granule strength was 628.3 ± 38.9 N [14]. Poultry manure with litter granules has shown better results.…”
Section: Resultsmentioning
confidence: 96%
“…This could have been caused by uneven weed density, different species composition, and low competition for nutrients. Mieldazys et al [27] found that cattle manure significantly increased the total number of productive stems per plant, making the crop denser and weed suppression stronger. Having compared the total weediness of spring wheat (2016) and winter wheat (2015), we found that the number of weeds (cereal growth stage BBCH 27 and 75) and the dry weight of weeds (cereal growth stage BBCH 75) decreased marginally after the application of plant-based manure.…”
Section: Spring Wheatmentioning
confidence: 99%
“…In general, the agriculture and food industries showcase several possibilities for their fruitful integration [40][41][42][43][44][45][46][47]. Within the aforementioned framework, we propose an integrated approach that allows valorising both agricultural and wool residues; Figure 1 graphically summarises its logic.…”
Section: Introductionmentioning
confidence: 99%